One-sample quantitative and two-sample qualitative faecal immunochemical tests for colorectal cancer screening: a cross-sectional study in China. Issue 5 (19th May 2022) - Wang, Le; Chen, Hongda; Zhu, Yunfeng; Lu, Ming; Wang, Youqing; Chen, Xinmin; Ma, Weihua; Du, Lingbin; Chen, Wanqing
Abstract : Objectives: Quantitative faecal immunochemical tests (FITs) are widely used for colorectal cancer (CRC) screening in the Western countries, whereas qualitative FITs are preferred in China. The present study aimed to compare the screening yield between one-sample quantitative FIT and two-sample qualitative FIT for CRC screening. Design: A cross-sectional study. Setting: A population-based CRC screening programme was conducted in 28 communities in Haining City, Zhejiang Province, China. Participants: Consecutive participants aged 40–74 years were invited to undergo the CRC screening programme. Two-sample qualitative FITs were offered between January 2019 and December 2019, and one-sample quantitative FIT was offered between August 2019 and February 2020. Primary and secondary outcome measures: Primary outcomes were detection rates of advanced neoplasms, including CRCs and advanced adenomas. Secondary outcomes were positivity rates and colonoscopy resource demand for the two FITs. The positivity thresholds were 20 µg and 1–5 µg haemoglobin per gram of faeces for the quantitative and qualitative FITs, respectively. Results: A total of 19 131 and 28 804 invitees were assigned to the two-sample qualitative and one-sample quantitative groups, respectively. Positivity rates were 14.2% for the two-sample qualitative FIT and 5.4% for the one-sample quantitative FIT. Detection rates of advanced colorectal neoplasms at colonoscopy using one-sample quantitative FIT and two-sample qualitative FIT were 17.6% (95% CI: 14.6% to 20.6%) and 10.5% (95% CI: 8.7% to 12.4%), respectively. Both detection rates of cancer and advanced adenoma were higher in the one-sample quantitative FIT group than those in the two-sample qualitative FIT group. Moreover, one-sample quantitative FIT significantly reduced the colonoscopy load for detection of one advanced neoplasm case (5, 95% CI: 5 to 7) than the two-sample qualitative FIT (10, 95% CI: 8 to 11). Conclusions: The one-sample quantitative FIT for CRC screening increases the detection rate of advanced neoplasia and reduces the colonoscopy workload compared with the two-sample qualitative FIT.